The Optimization of Calcareous Fly Ash‐Added Cement Containing Grinding Aids and Strength‐Improving Additives - Kaplan, Gökhan; Yildizel, Sadık Alper; Memiş, Selçuk; Öztürk, Ali Uğur (Wiley, 2018)
This is an experimental study which explores the physical, mechanical, and economic factors involved in the production of type CEM II A‐B/W cement. In this context, 4 cement additives were used in two different dosages (200 and 800 g/t). Class C fly ash was used for composite cement production at ratios of 5%, 20%, and 35%. It was shown that Blaine fineness increases with the increasing fly ash content. The use of fly ash at ratios of 5% and 20% was not found to have any unfavorable effects on the compressive strength at the early days. It is found that the use of additive for improving the early‐age strength is preferable when fly ash is used. It is possible to produce Class 52.5 N cement using additives to improve early strength and 20% fly ash. Loss in strength was observed in cement mortars produced using glycol‐based grinding aid. Increasing the dosage of chemical additive also led to loss in strength due to nonhomogeneous distribution of hydration products. As a result, grinding fly ash with clinker and the use of cement chemicals contribute to the cement sector in terms of sustainability. It is possible to produce cements with improved mechanical properties especially with the use of 20% fly ash.
Keywords: TA1-2040; Engineering (General). Civil engineering (General); 12. Responsible consumption